Efektivitas Penerapan Metode Field Trip terhadap Kemampuan Menulis Karangan Deskripsi Siswa - Sulastri Ningsih (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2021)
This study aims to determine the effectiveness of applying the field trip method on the ability to write descriptive essays of class VIII students of SMP Negeri H Wukirsari. The research design used an experimental approach with a quasi-experimental research type. The results showed that t0 was 5.21, tt (1%) was 2.75 and tt (5%) was 2.04. In conclusion, the application of the field trip method is practical on the ability to write descriptive essays of class VIII students of SMP Negeri H Wukirsari. Keywords: Description, Field Trip, Writing